“ANALISIS REAKSI PENGUMUMAN SAHAM BONUS TERHADAP RETURN DAN ABNORMAL RETURN DI BURSA EFEK INDONESIA 2000-2012” - Faris Ardiansyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study examines return and abnormal return with the anouncement of bonus share issues by companies listed on Indonesian Stock Exchange over the period 2000 to 2012. The sampling method in this study using purposive sampling method, the sample of 59 companies. Event Study method is used to study the reaction to the announcement of bonus shares. Methods of data analysis used was paired sample t-test for mean (t test). The results showed no significant effect between pre-event to event, event to post event, and pre-event to post event announcement of bonus shares issues. Keywords: Event Study, Announcement of Bonus Share Issues, Returns, Abnormal Returns.